Peningkatan Hasil Belajar IPA-Fisika melalui Penggunaan Model Inquiry Based Learning - Muhtar, Ernawati (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2025)
This research is Classroom Action Research (PTK) which aims to improve science-physics learning outcomes for expansion material in class VIII students at SMP Negeri 17 Halmahera Selatan for the 2024/2025 academic year through the use of an Inquiry Based Learning model. The research was carried out collaboratively and participatively, carried out in two cycles. Data collection in this research was carried out using participant observation and written tests. Based on the research results, it was concluded that the application of the Inquiry Based Learning model can improve students' science and physics learning outcomes. This is supported by research data which shows an increase in the percentage of completeness of the written test taken at the second meeting in each cycle. During the pre- cycle, learning completeness was only 42.85%, after implementing cycle 1 actions using the Inquiry Based Learning model, the percentage of students' learning completeness increased to 71.42%, then in cycle 2 actions, students' learning completeness reached 100%. The use of the Inquiry Based Learning model can also increase the learning activities of class VIII students at SMP Negeri 17 HalmaheraSelatan for the 2024/2025 academic year. Student activities consist of cooperation, responsibility and tolerance. In cycle 1, students' learning activities obtained a final score of 62%, meaning that students' learning activities were in good criteria. In cycle 2 the final score of student learning activities reached 88% so it was in the very good criteria